Effectiveness of Using Gases for Water Purification with the Same Microbial Load - I. Z. Koval (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія, 2021)
Purpose of the study is to іnvestigate the effect of gases on the process of water purification from aerobic microorganisms (MO) with the same initial content in the aquatic medium and to identify the nature of the gas in the atmosphere in which the highest degree of destroyed microbial cells per unit volume of water is achieved.